Performance of natural sensitizers on TiO2 hollow nano sphere based solar cells. (2021) - John Peter, I.; Rajamanickam, N.; Vijaya, S.; Anandan, S.; Ramachandran, K.; Nithiananthi, P.
Abstract: Terminalia chebula, Rubia tinctorum and Biancaea sappan are used here as sensitizers on TiO2 hollow-sphere. Anatase-rutile TiO2 hollow-spheres were synthesized using carbon spheres template assisted method. Structural, shape and purity of the prepared TiO2 hollow-spheres are confirmed through XRD, SEM measurements. Absorbance spectra are used to analyze the spectral response of the sensitizers. From the J-V measurements, it is found that Terminalia chebula shows a better performance of open circuit voltage (VOC ) ∼ 0.47 V, short circuit current (JSC ) ∼ 0.11 mA/cm 2 and fill factor 40% compared to all others. The charge transfer resistance and life-time are investigated through Nyquist and Bode plots.